Eighth-grade creativity reveals insights into understanding global warming, prompting interventions for enhancement: Kreativitas siswa kelas delapan mengungkapkan wawasan untuk memahami pemanasan global, mendorong intervensi untuk peningkatan - Al-Amin, Mokhammad Bashorudin; Wulandari, Fitria Eka (Universitas Muhammadiyah Sidoarjo, 2024)
This quantitative study examines the creative abilities of eighth-grade students at SMP Muhammadiyah 10 Sidoarjo in addressing global warming issues. Conducted on June 21, 2023, with 43 participants, the research utilized a validated creative thinking skills test alongside literature reviews. Findings indicate varying levels of creativity among students, with the majority demonstrating high creativity overall but lower proficiency specifically concerning global warming topics, scoring at 35.47%. These results emphasize the importance of tailored interventions to enhance students' creative thinking skills, particularly in understanding complex scientific concepts like environmental sustainability, informing curriculum development and instructional strategies to foster creativity and environmental literacy. Highlight: Eighth-grade creativity varies, especially in global warming understanding. Interventions enhance student creativity in complex scientific concepts. Findings guide curriculum for fostering creativity and environmental literacy. Keyword: Creativity, Eighth-grade students, Global warming, Education, Curriculum development